Crystal structures of two functionally different thioredoxins in spinach chloroplasts - Capitani, Guido; Markovi-Housley, Zora; del Val, Gregorio; Morris, May; Jansonius, Johan N.; Schürmann, Peter (My University, 2000)
Thioredoxins are small ubiquitous proteins which act as general protein disulfide reductases in living cells. Chloroplasts contain two distinct thioredoxins (•f and m) with different phylogenetic origin. Both act as enzyme regulatory proteins but have different specificities towards target enzymes. Thioredoxin f (Trx f), which shares only low sequence identity with thioredoxin m (Trx m) and with all other known thioredoxins, activates enzymes of the Calvin cycle and other photosynthetic processes. Trx m shows high sequence similarity with bacterial thioredoxins and activates other chloroplast enzymes. The here described structural studies of the two chloroplast thioredoxins were carried out in order to gain insight into the structure/function relationships of these proteins. Crystal structures were determined for oxidized, recombinant thioredoxin f (Trx f-L) and at the N terminus truncated form of it (Trx f-S), as well as for oxidized and reduced thioredoxin m (at 2.1 and 2.3 Å resolution, respectively). Whereas thioredoxin f crystallized as a monomer, both truncated thioredoxin f and thioredoxin m crystallized as non-covalent dimers. The structures of thioredoxins f and m exhibit the typical thioredoxin fold consisting of a central twisted five-stranded β-sheet surrounded by four α-helices. Thioredoxin f contains an additional α-helix at the N terminus and an exposed third cysteine close to the active site. The overall three-dimensional structures of the two chloroplast thioredoxins are quite similar. However, the two proteins have a significantly different surface topology and charge distribution around the active site. An interesting feature which might significantly contribute to the specificity of thioredoxin f is an inherent flexibility of its active site, which has expressed itself crystallographically in two different crystal forms.